Sectoral Governance under the EU's Bilateral Agreements and the Limits of Joint Institutional Frameworks: Insights from EU-Swiss Bilateralism for Post-Brexit Relations with the UK - Sandra Eckert (JCMS: Journal of Common Market Studies, 2022)
Joint Institutional Frameworks governing the EU's relations with third countries often fail to address important issues of sectoral governance. Non-EU countries benefit from access to EU sectoral bodies, but this is limited, and alternative avenues of co-operation are therefore needed. This article contributes to existing research on EU bilateral relations, which has thus far not paid sufficient attention to the external face of sectoral governance. The qualitative case comparison studies the well-established, yet increasingly politicized bilateral co-operation with Switzerland in order to draw insights for UK–EU relations, and contrasts two strategically important areas of market integration, namely electricity and financial markets. The findings show that politicization and (external) disintegration have repercussions for allegedly `technical' areas of co-operation where formalized requirements for EU sectoral bodies, public and private, become more stringent and less permissive to accommodate informal modes of co-operation that in the past facilitated external participation.
Keywords: 330; bilateral relations; equivalence; disintegration; private governance; informal governance